Pengaruh Kepuasan Kerja, Kompensasi Dan Komitmen Organisasi Terhadap Turnover Karyawan Dengan Masa Kerja Sampai Umur 38 Tahun Pada Bank Nagari Cabang Utama Padang - Ilham Rizki; Khairil Aswan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Human resources (HR) are the only important asset in an organization that can drive the work of other resources. In this organization, there is a system that has been regulated by a particular organization and human activities that work together to achieve organizational goals. An organization is also said to be a coordination of the activities of a number of people to achieve several common goals through the division of jobs (job descriptions) and functions through authority and responsibility. By coordinating the work and activity functions of each human resource, they will be able to achieve optimal results which will affect all lines in the company as a whole.